2017
DOI: 10.3389/fmicb.2017.02307
|View full text |Cite
|
Sign up to set email alerts
|

Wuji Wan Formula Ameliorates Diarrhea and Disordered Colonic Motility in Post-inflammation Irritable Bowel Syndrome Rats by Modulating the Gut Microbiota

Abstract: Emerging evidence suggests that gut microbiota contribute to the treatment of post-inflammatory irritable bowel syndrome (PI-IBS). Our previous studies have demonstrated that a Chinese formula, Wuji Wan, has the ability to mitigate abdominal pain and diarrhea in PI-IBS rats. However, little is known about the underlying mechanism and whether the gut microbiota mediate the effect of Wuji Wan on PI-IBS. Thus, the aim of this study was to determine whether Wuji Wan mitigated PI-IBS by modifying the gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 47 publications
(49 reference statements)
1
22
0
Order By: Relevance
“…Parasutterella is an anaerobic, asaccharolytic Gram-negative, non-spore-forming coccobacillus, that was originally described based on a strain isolated from a fecal sample from a healthy Japanese male [ 18 ]. Deep sea water (DSW) is one of several dietary supplements that tend to increase Parasutterella levels [ 19 22 ]. Using a diet-induced hamster model of hypercholesterolemia, Lin and colleagues demonstrated that DSW also led to significant reductions in triglycerides, LDL, and total cholesterol, although Bacteroidetes was the only bacterial population significantly correlated with serum cholesterol and LDL in response to the high cholesterol diet [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parasutterella is an anaerobic, asaccharolytic Gram-negative, non-spore-forming coccobacillus, that was originally described based on a strain isolated from a fecal sample from a healthy Japanese male [ 18 ]. Deep sea water (DSW) is one of several dietary supplements that tend to increase Parasutterella levels [ 19 22 ]. Using a diet-induced hamster model of hypercholesterolemia, Lin and colleagues demonstrated that DSW also led to significant reductions in triglycerides, LDL, and total cholesterol, although Bacteroidetes was the only bacterial population significantly correlated with serum cholesterol and LDL in response to the high cholesterol diet [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parasutterella is an anaerobic, asaccharolytic Gram-negative, non-spore-forming coccobacillus, that was originally described based on a strain isolated from a fecal sample from a healthy Japanese male [17]. Deep sea water (DSW) is one of several dietary supplements that tend to increase Parasutterella levels [18][19] [20] [21]. Using a diet-induced hamster model of hypercholesterolemia, Lin and colleagues demonstrated that DSW also led to signi cant reductions in triglycerides, LDL, and total cholesterol, although Bacteroidetes was the only bacterial population signi cantly correlated with serum cholesterol and LDL in response to the high cholesterol diet [19].…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia muciniphila is known to mediate a variety of host functions ranging from metabolism to immune regulation [21][22][23]. Regarding its role in pain syndromes or functional gastrointestinal disorders, A. muciniphila was found to be signi cantly reduced in children with IBS [24] as well as in animal models of post-in ammatory IBS [25]. Recently, Guida et al reported that pain related to dysbiosis in vitamin D de cient mice were ameliorated by an anandamide congener, in concomitance with increased levels of Akkermansia, Eubacterium and Enterobacteriaceae [26].…”
Section: Discussionmentioning
confidence: 99%